Role of Striatal-Enriched Tyrosine Phosphatase in Neuronal Function. (12th April 2016) - Kamceva, Marija; Benedict, Jessie; Nairn, Angus C.; Lombroso, Paul J.
Abstract : Striatal-enriched protein tyrosine phosphatase (STEP) is a CNS-enriched protein implicated in multiple neurologic and neuropsychiatric disorders. STEP regulates key signaling proteins required for synaptic strengthening as well as NMDA and AMPA receptor trafficking. Both high and low levels of STEP disrupt synaptic function and contribute to learning and behavioral deficits. High levels of STEP are present in human postmortem samples and animal models of Alzheimer's disease, Parkinson's disease, and schizophrenia and in animal models of fragile X syndrome. Low levels of STEP activity are present in additional disorders that include ischemia, Huntington's chorea, alcohol abuse, and stress disorders. Thus the current model of STEP is that optimal levels are required for optimal synaptic function. Here we focus on the role of STEP in Alzheimer's disease and the mechanisms by which STEP activity is increased in this illness. Both genetic lowering of STEP levels and pharmacological inhibition of STEP activity in mouse models of Alzheimer's disease reverse the biochemical and cognitive abnormalities that are present. These findings suggest that STEP is an important point for modulation of proteins required for synaptic plasticity.